2017
DOI: 10.1177/0098628317727907
|View full text |Cite
|
Sign up to set email alerts
|

What Constitutes Poor Teaching? A Preliminary Inquiry Into the Misbehaviors of Not-So-Good Instructors

Abstract: Across three phases, we investigated college students’ perceptions of poor college teaching to develop a typology of poor teaching behaviors. In Phase 1, students generated a list of qualities representative of poor teaching. In Phase 2, another group of students assigned behavioral correspondents to these qualities, resulting in a list of 15 poor teaching qualities and their attendant misbehaviors. Finally, in Phase 3, yet another group of students generated a “top 5” list of qualities and behaviors that thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 9 publications
3
34
0
Order By: Relevance
“…Table 4 shows the remarkable consistency of these data across the three phases and provides a composite average across all three phases. Consistent with American students (Busler et al, 2017), Chinese students’ responses also reflected that a large percentage of their teachers have been excellent or above average. However, these data also indicate that for other teachers, there is ample room for improvement.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Table 4 shows the remarkable consistency of these data across the three phases and provides a composite average across all three phases. Consistent with American students (Busler et al, 2017), Chinese students’ responses also reflected that a large percentage of their teachers have been excellent or above average. However, these data also indicate that for other teachers, there is ample room for improvement.…”
Section: Resultsmentioning
confidence: 56%
“…We compared the results between the Busler et al (2017) findings and the current study and found that U.S. and Chinese college students shared 17 categories of their perceptions of the characteristics of instructors. As shown in Table 1, there were three U.S. qualities (i.e., exams not representative of material covered, uninterested in the class, and inability to accept feedback) that Chinese students did not mention, while four qualities (i.e., unfair to students, unethical, poor teaching attitude, and poor classroom environment) that Chinese students reported as separate characteristics.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…More recently, Busler et al (2017) attempted to create a typology of poor teaching qualities. Across three phases, the research explored undergraduates’ evaluations of what constitutes a poor teacher.…”
Section: Perceptions Of Ineffective Teachingmentioning
confidence: 99%